2020
DOI: 10.30684/etj.v38i12a.1565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating The Effects of Micro and Nano Size of Silica Filler on Asphalt Cement Properties

Abstract: This research study examines the practicability of using micro and nano size silica to improve the asphalt characteristics. Asphalt cement penetration grade of (60 /70) was prepared using (0%, 2%, 4% and 6%) of silica filler by weight of asphalt and investigated in terms of the softening point, penetration, and penetration index, viscosity, and ductility values. To modify the asphalt binder, the silica powder was mixed by a mechanical blender set at (2000) rpm at a mixing temperature of 140°C. However, the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The NSF-modified asphalt was prepared using low contents (2%, 4%, 6%, and 8%) and high contents (20%, 30%, 40%, and 50%) by bitumen weight. The base bitumen was mixed with NSF using a Silverson L5M-A high-speed shear mixer at a temperature of 160 o C and a shearing speed of 2000 rpm for 1 hr [23,25]. The homogeneity of modified asphalts was assessed using Scanning Electron Microscopy.…”
Section: Preparation Of the Nsf-modified Bindermentioning
confidence: 99%
See 1 more Smart Citation
“…The NSF-modified asphalt was prepared using low contents (2%, 4%, 6%, and 8%) and high contents (20%, 30%, 40%, and 50%) by bitumen weight. The base bitumen was mixed with NSF using a Silverson L5M-A high-speed shear mixer at a temperature of 160 o C and a shearing speed of 2000 rpm for 1 hr [23,25]. The homogeneity of modified asphalts was assessed using Scanning Electron Microscopy.…”
Section: Preparation Of the Nsf-modified Bindermentioning
confidence: 99%
“…In other studies, silica fume with contents of 2, 4, 6% by weight of binder was used to modify virgin bitumen. The results showed that the addition of SF improved the rheological-physical properties of the virgin bitumen [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Micro-sized fillers are widely used because of their costeffectiveness, ease of processing, or specific mechanical properties over the nanofillers. [40][41][42] For instance, DhilipKumar et al 43 conducted a study to analyze the impact of silicon carbide (SiC) nanoparticle reinforcement on shear properties of composite SLJ. The Results of the study revealed that the addition of 1.5 wt.% SiC nanoparticle increased shear strength of GFRP lap joints by 18.96% compared to SiC-free joints.…”
Section: Introductionmentioning
confidence: 99%
“…Proper dispersion is crucial for realizing the desired properties and performance of composite materials. Micro‐sized fillers are widely used because of their cost‐effectiveness, ease of processing, or specific mechanical properties over the nanofillers 40–42 . For instance, DhilipKumar et al 43 conducted a study to analyze the impact of silicon carbide (SiC) nanoparticle reinforcement on shear properties of composite SLJ.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of road pavement materials is one of the most serious issues that must be addressed in order to maintain the performance of road pavements (2). To minimize these effects, a variety of additives such as styrene-butadienestyrene, lime, rubber, and waste powders have been added to change controlling asphalt and improving the performance of asphalt binder (3). Surface rutting occurs as a result of the paving material's plastic deformation, as well as the subgrade's and overlay asphalt layer's general subsidence.…”
Section: Introductionmentioning
confidence: 99%